The correlation of physical development and results of the training process of young gymnasts - Vlasyuk A.O. ,; Bevza T.V. ,; Bedareva A.A. ,; Bakaev V.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluate the influence of compensatory exercises on the harmony of physical development and the efficiency of the body parts of young gymnasts as a single kinematic system. Methods and structure of the study. 24 young gymnasts aged 13.5±0.5 years with anthropometric indicators: height – 155.6±7.5 kg; weight – 48.4±7.5 cm; chest girth – 81.7±5.9 cm. A method was used based on the distribution of all variants of the studied indicator into ranges from minimum to maximum values. To train and assess the ability to muscle balance and joint flexibility, the following were used: Romberg test; Kraus-Weber test, leg abduction in the supine position; leaning forward while sitting; twisting of the torso; tilts to the side. Results and conclusions. The sporting achievements of young gymnasts at the age of 13 are largely determined by rational technique corresponding to morphological data, as well as biological development, the primary prerequisites of which are anthropometric characteristics. Compensatory exercises, used with a specialized focus on the development of the main muscle groups included in the kinetic links of performing gymnastic combinations, are one of the training options and can reduce the negative impact of unidirectional load on young gymnasts.